Synthesis, structural features, antibacterial behaviour and theoretical investigation of two new manganese(III) Schiff base complexes. (1st September 2018) - Paul, Pranajit; Bhowmik, Kanti R.N.; Roy, Subhadip; Deb, Dibakar; Das, Nandita; Bhattacharjee, Maitri; Dutta Purkayastha, R.N.; Male, Louse; Mckee, Vickie; Pallepogu, Raghavaiah; Maiti, Debasis; Bauza, Antonio; et al.
Graphical abstract: Manganese(III) Schiff base compounds, [Mn(L)(OCN)]2 (1 ), [Mn(L′)(H2 O)2 ][dnba]·DMF·H2 O (2 ) [H2 L = N, N ′- o -phenylenebis(salicylaldimine)] or H2 L′ [H2 L′ = N, N ′-bis(salicylidene)ethylenediamine], were prepared and characterized by spectroscopic and X-ray diffraction analysis. Theoretical study analyses noncovalent interactions in the complexes. Topological analysis of 2 reveals existence of binodal 3, 4-connected 2D net with the 3, 4L13 topology. Fluorescence and antibacterial properties of the compounds were also explored. Abstract: Two discrete manganese(III) coordination compounds, [Mn(L)(OCN)]2 (1 ) and [Mn(L′)(H2 O)2 ][dnba]·DMF·H2 O (2 ) bearing in situ generated Schiff base ligands H2 L [H2 L = N, N ′- o -phenylenebis(salicylaldimine)] or H2 L′ [H2 L′ = N, N ′-bis(salicylidene)ethylenediamine], were easily prepared by treating Mn(CH3 COO)2 ·4H2 O with salicylaldehyde and o -phenylenediamine (for 1 ) or ethylenediamine (for 2 ), and in the presence of supporting cyanate ligands or 3, 5-dinitrobenzoate (dnba) counter anions, respectively. The obtained products were isolated as air-stable crystalline solids and were fully characterized by spectroscopic methods, single-crystal X-ray diffraction, topological analysis, as well as theoretical methods. The X-ray diffraction of the compound 1 reveals that the structure is dimeric with phenolic oxygen atom acting as bridge between two symmetrically equivalent Mn(III) atoms. The structure of 2 contains mononuclear cationic [Mn(L′)(H2 O)2 ] units along with a 3, 5-dinitrobenzoate anion and crystallization DMF molecule. Structural analysis indicates a distorted octahedral geometry for both complexes. Intermolecular hydrogen bonding and π–π stacking interactions are present in the lattice and play an important role in cohesion of the structures. Topological analysis of the compound 2 reveals a binodal 3, 4-connected underlying 2D net with the 3, 4L13 topology. Noncovalent interactions were investigated in terms of energies and geometries using theoretical calculations. Fluorescence and antibacterial properties of 1 and 2 were also investigated and discussed.